2010
DOI: 10.1371/journal.pone.0011852
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Functional Benefit Following Transplantation of Motor Neuron Progenitors to the Injured Rat Spinal Cord

Abstract: BackgroundMotor neuron loss is characteristic of cervical spinal cord injury (SCI) and contributes to functional deficit.Methodology/Principal FindingsIn order to investigate the amenability of the injured adult spinal cord to motor neuron differentiation, we transplanted spinal cord injured animals with a high purity population of human motor neuron progenitors (hMNP) derived from human embryonic stem cells (hESCs). In vitro, hMNPs displayed characteristic motor neuron-specific markers, a typical electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 42 publications
5
83
0
Order By: Relevance
“…Our results showed that MSC-treated group presented a greater amount of neural stem cells (nestin+) at the lesion site than the control. Thus, cell transplantation may have influenced the injure environment to provide signaling and growth factors to proliferation of endogenous stem cells as established by Urdzikova et al (2006) and Rossi et al (2010). Also, Wu et al (2003) demonstrated functional recovery after transplantation of MSC and attributed this to increased differentiation of endogenous neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that MSC-treated group presented a greater amount of neural stem cells (nestin+) at the lesion site than the control. Thus, cell transplantation may have influenced the injure environment to provide signaling and growth factors to proliferation of endogenous stem cells as established by Urdzikova et al (2006) and Rossi et al (2010). Also, Wu et al (2003) demonstrated functional recovery after transplantation of MSC and attributed this to increased differentiation of endogenous neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether TDP-43 fragments and/or mutant forms have cytotoxic or cytoprotective effects on mature motor neurons, human ES cell-derived motor neurons were generated in vitro as reported previously. 20 In addition to positive staining of HB-9 and Islet-1 (89.4 AE 4.0% and 88.8 AE 9.3%, respectively), immunocytochemistry showed that 88.3 AE 7.8% and 56.8 AE 20.7% of the cells expressed bIII-tubulin, a marker for neurons, and non-phosphorylated neurofilament protein, a marker for mature neurofilaments, respectively. Meanwhile, just 4.9 AE 3.2% of the cells expressed glial fibrillary acidic protein (GFAP), a marker for astrocytes (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Transplanted motor neurons may replace the lost MNs. Studies have shown that transplanted ESCs derived MNs supported the endogenous neurons survival through secretion of beneficial growth factors in the SCI model [27], spinal muscular atrophy (SMA) and Amyotrophic lateral sclerosis (ALS) model [28]. Transplanted OPCs may differentiate into mature oligodendrocytes to myelinate both ESCs derived MNs and constitutive MNs.…”
Section: Discussionmentioning
confidence: 99%